Projecting the Number of Pupils and Classrooms in Public Primary Schools in South-western Nigeria (2020-2024) - O. O. Gambo; A. S. Adelokun (University of Sofia, 2020)
In the study, the number of pupils and classrooms in public primary schools in Southwestern Nigeria were projected by first calculating how many pupils and classrooms are available in the schools, how many pupils will be in the study area from the year 2021 to 2024, and then estimate the number of classrooms required from the year 2020 to 2024. The study adopted a survey research design. This study's population comprised 8401 public primary schools in Nigeria's six Southwestern states. The states consist of Lagos, Ogun, Oyo, Ekiti, Osun, and Ondo. The study sample comprised 1092 schools, using the Research Advisor. The purposive sampling technique was used to select three out of the six Southwestern states. The simple random sampling technique was employed in selecting the schools and their headteachers in each state. 370, 357, and 365 public primary schools and their headteachers were selected from Lagos, Ogun, and Oyo States, respectively. Two instruments were used to gather data for the study. These are an official education document and a questionnaire. An official document containing the primary data on pupils' flow was collected from Universal Basic Education Boards of Lagos, Oyo, and Ogun States to generate baseline enrolment figures to corroborate the schools provided the data under investigation. The questionnaire is titled "Primary School Pupils' Flow Questionnaire (PSPF-Q)", and it was used to elicit data on the number of pupils in the study area for the year 2020 and the number of classrooms physically available. The questionnaire was adapted from Adelokun & Adewole (2017). Therefore, the Primary School Pupils' Flow Questionnaire (PSPF-Q) was used to elicit data from headteachers on their pupils' flow from 2015/2016 session to 2020/2021 session. The results showed that public primary schools in Southwestern Nigeria would have an average of 464,836 pupils in 2021, an average of 479,944 pupils in 2022, 495,542 pupils in the year 2023, and an average number of 511,647 pupils in the year 2024. It also showed that the average number of classrooms required in the year 2020 is 3,172, for the year 2021, it is 3,659 for the year 2022, it equals 4,163, for the year 2023, it equals 4,683, and for the year 2024, it is 5,220. The study concluded that the government should plan for the projected number of pupils and classrooms.